2008
DOI: 10.1111/j.1471-0528.2008.01872.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sublingual versus vaginal misoprostol for the induction of labour: a systematic review

Abstract: Background The induction of full-term labour in women with a live fetus remains a major challenge in modern obstetrics.Objectives To determine, using the best level of evidence available, the efficacy and safety of sublingual administration of misoprostol compared with vaginal misoprostol in the third trimester of pregnancy for the induction of labour, according to initial doses, in women with a live, full-term fetus and an unripe cervix.Search strategy Pubmed/Medline, Lilacs and Scielo databases were consulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 22 publications
2
36
1
3
Order By: Relevance
“…Our search uncovered three systematic reviews comparing sublingual or buccal misoprostol with other methods of labour induction [24-26]. The Cochrane review by Muzonzini[24] and colleagues and the review by Bartusevicius and colleagues[25] both included the same three studies with a total of 507 women and reached similar conclusions.…”
Section: Pharmacologic Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Our search uncovered three systematic reviews comparing sublingual or buccal misoprostol with other methods of labour induction [24-26]. The Cochrane review by Muzonzini[24] and colleagues and the review by Bartusevicius and colleagues[25] both included the same three studies with a total of 507 women and reached similar conclusions.…”
Section: Pharmacologic Methodsmentioning
confidence: 95%
“…This review included five studies with 740 subjects [26]. The authors found no significant differences in the rates of vaginal delivery not achieved within 24 hours, hyperstimulation, or cesarean deliveries.…”
Section: Pharmacologic Methodsmentioning
confidence: 99%
“…Misoprostol is used for inducing birth and most of the times in high risk gestations with associated disease, particularly pregnancy hypertension syndromes. 20 Oxytocin, on its turn, is frequently used for inducing and conducting labor. 21 Probably due to the low frequency of patients using misoprostol included in this study, no association with episiotomy was found.…”
Section: Discussionmentioning
confidence: 99%
“…16,18 Caesarean section rate in other studies were much higher than in our study. 18,19 were reported by other studies. 16,18 It has been speculated that direct effect of vaginal misoprostol on the cervix might contribute to excessive uterine activity, FHR abnormalities and higher rate of meconium stained liquor.…”
Section: Introductionmentioning
confidence: 54%